Genetic variability within Phaeoisariopsis griseola from Central America and its implications for resistance breeding of common bean - Mahuku, George S.; Jara, Carlos E.; Cuásquer, Juan B.; Castellanos, G. (Wiley, 2002)
The genetic and virulence variability of 112 isolates of Phaeoisariopsis griseola, collected from various locations in Central America, were studied using seven random amplified polymorphic DNA (RAPD) primers and 12 common-bean differential genotypes. Broad molecular diversity (H = 0·92) among isolates was found using RAPD markers. Fifty pathotypes were identified on 12 differential bean genotypes, 29 of which were represented by only one isolate. Only 18 pathotypes were found in two or more countries. Pathotype 63-63 was the most virulent and caused leaf spots on all 12 common-bean differential genotypes. Comparison of virulence phenotypes and RAPD profiles to known Andean P. griseola isolates confirmed that all isolates belonged to the Mesoamerican group. Pairwise comparison between individual RAPD loci showed that the majority were in gametic phase linkage disequilibrium, revealing that P. griseola maintains a genetic structure that is consistent with asexual reproduction. The molecular and virulence diversities of P. griseola isolates from Central America imply that using single resistance genes to manage angular leaf spot is inadequate and stacking resistance genes may be necessary to manage the disease effectively.